Activism mergers - Boyson, Nicole M.; Gantchev, Nickolay; Shivdasani, Anil (Journal of Financial Economics, 2017)
Shareholder value creation from hedge fund activism occurs primarily by influencing takeover outcomes for targeted firms. Controlling for selection decisions, activist interventions substantially increase the probability of a takeover offer. Third-party bids for targets have higher returns, premia, and completion rates, but these patterns reverse when the activist is the bidder. Failed bids for activism targets lead to improvements in operating performance, financial policy, and positive long-term abnormal returns, suggesting that activism enhances value. The positive long-term performance from hedge fund activism arises from monitoring target management during merger and acquisition contests and not from target undervaluation or bidder overpayment.